The development of engineering graphic for furniture studio - Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Ahmad Rasdan Ismail; Md. Baharuddin Abdul Rahman (AENSI, 2015)
Project-oriented learning is a main approach which implement in workshop furniture, Faculty of Creative Technology and Heritage, University Malaysia Kelantan (UMK). However, the implementation of project-oriented approach is undirected and just expect to lecturer and student initiatives without appropriate guidelines, particularly in the application of engineering processes. Workflow-based engineering is important in learning furniture making. Workflow can be driven right through the systematic and methodical process. Therefore, engineering graphics module has been designed and developed to provide guidance to students in performing the work properly and indirectly the self-directed learning through project-oriented learning approach can be implemented more better and effectively.